Formulation & InVitro Evaluation of Controlled Release Tablets of Oxcarbazepine - N.Phrudvish; T.Malyadri; Ch.Saibabu (International Journal of Indigenous Herbs and Drugs, 2021)
The present research project aimed to develop a Control release oral Oxcarbazepine tablets by using Polymers like Tamarind gum, Xanthan gum, HPMC K4M, and HPMC K 15M were used for controlling the drug release, and the polymers are mixed in a predetermined ratio. Totally 12 formulations were prepared and evaluated for pre-compression and post-compression parameters, and all the results were found to be within the limits. From the drug and excipients compatibility studies(FT-IR) it was confirmed that the drug and excipients have any interactions. The in vitro dissolution studies revealed that the F12 formulation containing 18% of HPMC K4M & 18% of HPMC K15M controls the drug release up to 12hours. So F12 formulation was considered to be suitable for the formulation of Oxcarbazepine controlled-release tablets at 18% concentration of HPMC K4M & 18% concentration of HPMC K15M and the drug release kinetics revealed that the F12 formulation shows a super case II transport mechanism.